SERBIAN ORGANIC FOOD CONSUMER PROFILE – CONTRADICTIONS OF PREVIOUS RESEARCHES AND METHODOLOGICAL POSSIBILITIES - Grubor, Aleksandar; Đokić, Nenad S.; Milićević, Nikola (International Journal of Economic Practice and Policy, 2019)
Previous research of organic food consumers, both in the world and in domestic conditions, failed to determine the unique characteristics of the profiles of these consumers. Among various reasons that could cause this condition, one is insufficient knowledge and / or use of all methodological potentials of a statistical instrumentarium. This paper deals with the two previously mentioned topics - showing the inconsistency of the description of the organic food consumers profile in recent domestic research, and pointing out the need to include the interaction of the variables that are descriptors of segments by recalling foreign research practice. The importance of the work is in potential elimination of part of possible contradictions of future research, which can have significant implications for all stages in the marketing management process of organic food suppliers.